1993
DOI: 10.3109/00498259309059450
|View full text |Cite
|
Sign up to set email alerts
|

Dose-response relationships for the induction of P450 2B by 1,4-bis[2-(3,5-dichloropyridyloxy)]benzene (TCPOBOP) in rat and cultured rat hepatocytes

Abstract: 1. The dose-response relationships for hepatic CYP2B induction by 1,4-bis[2-(3,5-dichloropyridyloxy)]benzene (TCPOBOP) were examined in the male F344/NCr rat. TCPOBOP, administered for 14 days at 0-1000 ppm in the diet, caused concentration-dependent induction of hepatic CYP2B1 protein and RNA, and of CYP2B-mediated catalytic activities (benzyloxy- and pentoxyresorufin O-dealkylation, and testosterone 16 beta-hydroxylation). ED50 values for CYP2B induction were > or = 300 ppm dietary TCPOBOP. The maximal induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Subsequent studies using a humanized PXR mouse model and human cell lines further indicated that hPXR also regulates UGT1A1 expression [25, 36]. GST, another phase II conjugation enzyme, can be induced modestly by rifampicin [37], as well as by phenobarbital [38] and TCPOBOP [39], suggesting that PXR and CAR might regulate the expression of GSTs. Murine GST genes such as Gsta1, Gstm1, and Gstm2 have been shown to be regulated by both mPXR and mCAR [16, 40].…”
Section: Pxr and Car In Xenobiotic Detoxificationmentioning
confidence: 99%
“…Subsequent studies using a humanized PXR mouse model and human cell lines further indicated that hPXR also regulates UGT1A1 expression [25, 36]. GST, another phase II conjugation enzyme, can be induced modestly by rifampicin [37], as well as by phenobarbital [38] and TCPOBOP [39], suggesting that PXR and CAR might regulate the expression of GSTs. Murine GST genes such as Gsta1, Gstm1, and Gstm2 have been shown to be regulated by both mPXR and mCAR [16, 40].…”
Section: Pxr and Car In Xenobiotic Detoxificationmentioning
confidence: 99%
“…The striking potency of TCPOBOP in the mouse, together with the demonstration that certain structural features are required for activity within this class of agents (20,21), led to the hypothesis that a separate, high-affinity response element (receptor) for the bis(pyridy1oxy)benzenes existed in the mouse but not in the rat (17,18). More recently, however, we have demonstrated that most of the manifestations (CYP2B, CYP3A, epoxide hydrolase) of the phenobarbital-type response ure highly induced in the rat by TCPOBOP when the xenobiotic is administered continuously in the diet (22). Thus, the maximal CYP2B induction responses detected in rats exposed to a diet containing 1000 ppm TCPOBOP are 60430% of those evoked by 500 ppm phenobarbital, and the induction potency based on serum TCPOBOP levels appears to be as great as or greater than that of phenobarbital (22).…”
Section: -Dealkylation Activities Lmmunoreativementioning
confidence: 99%
“…More recently, however, we have demonstrated that most of the manifestations (CYP2B, CYP3A, epoxide hydrolase) of the phenobarbital-type response ure highly induced in the rat by TCPOBOP when the xenobiotic is administered continuously in the diet (22). Thus, the maximal CYP2B induction responses detected in rats exposed to a diet containing 1000 ppm TCPOBOP are 60430% of those evoked by 500 ppm phenobarbital, and the induction potency based on serum TCPOBOP levels appears to be as great as or greater than that of phenobarbital (22). These findings suggest that similar response mechanisms for phenobarbital-type inducers, including TCPOBOP, exist in the two rodent species.…”
Section: -Dealkylation Activities Lmmunoreativementioning
confidence: 99%
“…In mammals, PB and a number of structurally diverse xenobiotics, including the highly potent 1,4-bis [2-(3,5-dichloropyridyloxy)] benzene (TCPOBOP) and ortho -substituted polychlorinated biphenyl (PCB) congeners, strongly induce the expression of members of the CYP2B subfamily (Kopec et al, 2010; Nims et al, 1993; Smith et al, 1993a, 1993b; Vezina et al, 2004; Waxman, 1999). There is a long history of efforts to identify and demonstrate a CYP2B-like induction by PB or related compounds in fish (Bainy et al, 1999; Buhler and Wang-Buhler, 1998; Celander et al, 1996; Elskus and Stegeman, 1989; Förlin, 1980; GoksĂžyr, 1985; Iwata et al, 2002; Kleinow et al, 1990; Klotz et al, 1986; Stegeman et al, 1990).…”
Section: Introductionmentioning
confidence: 99%